2005
DOI: 10.1175/jtech1775.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Small-Scale Variability of Precipitation Using an Imaging Radar

Abstract: For many years, spatial and temporal inhomogeneities in precipitation fields have been studied using scanning radars, cloud radars, and disdrometers, for example. Each measurement technique has its own advantages and disadvantages. Conventional profiling radars point vertically and collect data while the atmosphere advects across the field of view. Invoking Taylor's frozen turbulence hypothesis, it is possible to construct time-history data, which are used to study the structure and dynamics of the atmosphere.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…It should be noted that, for this study, the accuracy and precision of interest is not absolute, but is relative to the optimal measurements provided by the imaging radar. Coherent radar imaging (CRI) was developed to reconstruct a two-dimensional, angular distribution of the atmospheric structure within the volume illuminated by the transmitted beam (e.g., Kudeki and Sürücü 1991;Palmer et al 1998;Yu et al 2000;Hélal et al 2001). In addition, the angular distribution of radial velocity can be obtained by an efficient algorithm (Cheong et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, for this study, the accuracy and precision of interest is not absolute, but is relative to the optimal measurements provided by the imaging radar. Coherent radar imaging (CRI) was developed to reconstruct a two-dimensional, angular distribution of the atmospheric structure within the volume illuminated by the transmitted beam (e.g., Kudeki and Sürücü 1991;Palmer et al 1998;Yu et al 2000;Hélal et al 2001). In addition, the angular distribution of radial velocity can be obtained by an efficient algorithm (Cheong et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Using adaptive array processing, threedimensional volumetric images can be constructed within the field of view with a temporal resolution of approximately 2.5 s (Lopez-Dekker and Frasier 2004;Cheong et al 2004). In addition to imaging clear-air turbulence, the TEP radar has been used for studies of the interaction of precipitation with turbulence (Palmer et al 2005). Using adaptive methods, CRI also holds promise for the mitigation of both ground and biological clutter contamination (Cheong et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Chau and Woodman (2001) also showed the angular distribution using the Fourier-based method, Capon method, MEM, and the fitting technique. Using the characteristic that raindrop fall velocity is much greater than vertical wind velocity, Palmer et al (2005) demonstrated that fine-scale angular distributions of backscattered power from clear air and that from raindrops are able to be obtained separately. From a CRI measurement by TEP, Pollard et al (2000) demonstrated that horizontal distribution of refractive index structure function is able to be measured.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Usually, we can identify atmospheric and precipitation echoes in the Doppler spectra, and employ the moment method to estimate the atmospheric and precipitation parameters (e.g., echo power, Doppler velocity, and spectral width). In the time domain, however, Palmer et al (2005) used high-pass and low-pass filters to separate atmospheric and precipitation echoes and explored the effects of turbulence on precipitation. In a different way, Williams (2012) conducted a campaign with VHF and UHF radars, and separated hydrometeor motions, to which the UHF radar is sensitive, from the echo spectra of the VHF radar.…”
Section: Introductionmentioning
confidence: 99%